Turkish-Iranian Relations in a Changing Middle East - Larrabee, F. Stephen (RAND Corporation, 2013)
Turkey and Iran tend to be rivals rather than close partners, despite sharing certain economic and security interests. For instance, Turkey supports the opposition in Syria, while Iran supports the regime. Turkey is further concerned about a possible nuclear arms race in the Middle East. U.S. and Turkish interests in the region closely overlap, but the United States should not expect Turkey to follow its policy toward Iran unconditionally.